EDUCATION ENDOWMENT FUND GOVERNANCE: A QUALITATIVE STUDY OF POLICY IMPLEMENTATION IN BOJONEGORO, INDONESIA - Cipto Roso; Suyanto Suyanto; M. Furqon Wahyudi (STKIP PGRI Situbondo, 2026)
Education endowment funds are increasingly promoted as sustainable financing instruments to support long-term educational development, particularly within decentralized governance systems. However, empirical evidence on how such funds are governed and implemented at the local level remains limited. This study examines the governance of the Education Endowment Fund in Bojonegoro Regency, Indonesia, focusing on the translation of policy intentions into institutional practices and school-level utilization. Drawing on qualitative data from in-depth interviews and policy document analysis, the study finds that although the fund operates within a formally structured governance framework, its implementation is characterized by centralized decision-making, compliance-oriented accountability mechanisms, and constrained local agency. Consequently, the fund is largely utilized to address short-term operational needs rather than to advance long-term sustainability objectives. The findings also reveal the importance of informal coordination and adaptive practices in navigating administrative complexity, albeit with uneven outcomes across institutions. This study contributes to debates on education financing governance by highlighting the critical role of local governance dynamics in shaping policy outcomes.